A retrospective clinical trial on nasal bone fractures admitted to a level three emergency room (Annals of Medical Research, 2021)
Aim: The anatomical location and protruding structure of the nasal bone can easily lead to fracture as a result of trauma. The high incidence rates have emphasized that the causes, treatments, and complications of these fractures should be investigated. The purpose of this study is to investigate our treatment modalities and complications by reviewing the current information about such fractures.Material and Methods: A total of 582 patients presented with nasal bone fractures between January 2014 and December 2019 were retrospectively analyzed. Examination findings, patient records, and radiological examinations of fractures were analyzed in detail.Results: The age of the patients was between 2 and 83 years (mean age: 33.9 ± 6.11 years). The study included 451 (77.5%) males and 131 (22.5%) females. The most common etiologic factor was assault (35.7%). The most common postoperative complications included deformity (53 patients; 9.1%), nasal congestion (41 patients; 7.1%), and smell disorders (5 patients; 0.9%), with the complications increased with the severity of fracture.Conclusion: Reduction procedures are successfully performed within the first 2 weeks following nasal fractures, and if there is a suspicion of causing deformity in patients under observation, necessary surgical interventions should be performed.
Keywords: Complication; nasal fracture; reduction; trauma